Isolation of OXA-48-like carbapenemase-producing Escherichia coli susceptible to piperacillin/tazobactam in a Japanese patient without a history of travel abroad. Issue 5 (May 2023) - Kaneko, Masahiko; Masuda, Yuya; Sawachika, Hiroshi; Shikata, Hisaharu; Moriyama, Chie; Miura, Minako; Yamamoto, Hisato; Nakamura, Taro; Fukumoto, Komami; Utsunomiya, Yasushi; Sakai, Kyoko; Ito, Yuri; et al.
Abstract: Oxacillinase (OXA)-48-like β-lactamases are the most common carbapenemases in Enterobacterales in certain regions of the world and are being introduced on a regular basis into regions of non-endemicity. Japan has been characterized by low rates of carbapenemase-producing Enterobacterales, and among them, OXA-48-like carbapenemase-producing isolates are extremely rare. Here we describe a Japanese medical worker, without a history of travel abroad, who was diagnosed as having a community-acquired urinary tract infection, and whose urine sample was found to be positive for OXA-48-like carbapenemase-producing Escherichia coli . None of her close contacts had a history of foreign travel, and the same drug-resistant organism was not observed in other patients who had been hospitalized and undergone environmental culture tests in the same medical institution. This isolate was resistant to penicillins, narrow-spectrum cephalosporins, fluoroquinolones, and cefmetazole, but was susceptible to broad-spectrum cephalosporins, piperacillin/tazobactam, and meropenem and displayed reduced susceptibility to imipenem. The modified carbapenem inactivation test supported carbapenemase production, but inhibitor-based synergistic tests yielded negative results of carbapenemase production. Multiplex polymerase chain reaction revealed the presence of the carbapenemase gene ( bla OXA-48 ) bla TEM and AmpC β-lactamase gene ( bla DHA ). Singleplex polymerase chain reaction targeting the bla OXA-48 region amplified a product sequencing to nearly the full length (722 bp) and matching 100% with OXA-48. The present case highlights a new concern regarding OXA-48-like carbapenemase-producing Enterobacterales, which remain challenging to detect for clinical laboratories in regions of non-endemicity, and may already be latent in Japan.